Instrument Test Kinematics: How Velocity and Acceleration Vectors Captured by High School Students - Nukhba, Rania; Sutopo, Sutopo; Wisodo, Hari (Kasuari: Physics Education Journal (KPEJ), 2024)
Vectors in kinematics are rarely highlighted in high school. Even though vectors are the language used by physicists. This study aims to determine the validity and reliability of the test instrument developed and to explore the ability of vectors in kinematics of high school students. The method used in this research is research and development of the 4D model. The developed test instrument for vectors in kinematics is in the form of multiple choice with an arrow direction accompanied by a command to describe the vector and explain the reason for choosing the vector direction. The test instrument covers one- and two-dimensional kinematics topics by highlighting the concepts of velocity and acceleration. Two-dimensional kinematics is divided into constant velocity and increasing velocity. This test instrument consists of thirteen questions with an average point-biserial coefficient of 0.493 and KR-20 of 0.784. Then, this test instrument was used to measure the vector ability in kinematics of high school students with a sample size of sixty-seven students. It was found that most high school students had difficulty in acceleration as two-dimensional vector, acceleration as one-dimensional vector, and velocity as one-dimensional vector with few obstacles. Learning with the method of integrating vectors in kinematics has the possibility to solve this problem.